The Influence of Geographical Conditions on the Optimization of Cost and Time in Construction Projects in Island Regions of Maluku Province (Case Study: Road Preservation Project on Liran Island) - Sangadji, Cindy; Yuwono, Bambang Endro; Inavonna, Inavonna; Pontan, Darmawan (Eduvest - Journal of Universal Studies, 2026)
The Road Preservation Project on Liran Island has faced significant implementation delays. Liran Island, categorized as one of the 3T (terdepan, tertinggal, and terluar) areas, has encountered challenges mainly due to difficult geographical conditions. These challenges include shallow sea topography and shoals that hinder navigation, strong currents and tides that limit ship movement, adverse weather conditions such as high winds and large waves, and limited resources that require material imports from outside the island. This study aims to identify and analyze the geographical factors most influencing the optimization of costs and time in the project. The research design employs simulation of optimization scenario models, comparing geographical and normal conditions (without geographical factors). Data analysis is conducted using the Transportation Method for cost optimization (material procurement) and the Critical Path Method (CPM) for time optimization (rescheduling). The results reveal that geographical conditions significantly impact mobilization costs. Among the variables analyzed—sea topography (X1), sea and water conditions (X2), weather (X3), and natural resources (X4)—weather (X3), particularly wind speed and wave height, has the greatest influence on increasing distribution costs. Furthermore, geographical conditions also affect the project schedule, particularly in material delivery planning, which requires longer loading and unloading times. Adjusting the schedule based on geographical conditions leads to cost and time efficiencies, especially in choosing the right vessel types, estimating weather, and managing tidal conditions.